2010
DOI: 10.1021/ja105855v
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Addition of Lithium Diisopropylamide to Unsaturated Esters: Role of Rate-Limiting Deaggregation, Autocatalysis, Lithium Chloride Catalysis, and Other Mixed Aggregation Effects

Abstract: Lithium diisopropylamide (LDA) in tetrahydrofuran at −78 °C undergoes 1,4-addition to an unsaturated ester via a rate-limiting deaggregation of LDA dimer followed by a post-rate-limiting reaction with the substrate. Muted autocatalysis is traced to a lithium enolate-mediated deaggregation of the LDA dimer and the intervention of LDA-lithium enolate mixed aggregates displaying higher reactivities than LDA. Striking accelerations are elicited by <1.0 mol % LiCl. Rate and mechanistic studies reveal that the uncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
95
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 96 publications
1
95
0
6
Order By: Relevance
“…11 Previous studies showed that the metalation of oxazolidinone 1 with LDA in THF or THF/hexane mixtures at −78 °C proceeds according to Scheme 1. 8 Intermediate mixed dimer 8 is also observable with excess LDA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Previous studies showed that the metalation of oxazolidinone 1 with LDA in THF or THF/hexane mixtures at −78 °C proceeds according to Scheme 1. 8 Intermediate mixed dimer 8 is also observable with excess LDA.…”
Section: Resultsmentioning
confidence: 99%
“…LDA, [ 6 Li]LDA, and [ 6 Li, 15 N]LDA were prepared as described previously. 11 Solutions of LDA were titrated for active base with a literature method. 41 Air- and moisture-sensitive materials were manipulated under argon with standard glove box, vacuum line, and syringe techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Collum et al wisely caution all users of commercial lithium reagents to be alert to the possible influence of LiCl contamination stressing that source and batch dependency could be a problem and potentially costly in larger-scale process chemistry. In a subsequent study significantly not probing deprotonation but nucleophilic addition reactions of LDA (with unsaturated esters), [4] Collum et al detected similar rate enhancements caused by as little as 1.0 ppm of LiCl. This same occurrence in two distinct types of LDAexecuted reaction focuses thoughts on the likelihood of a shared substrate-independent process at least in part, which Collum et als rigorously conducted kinetic measurements suggest could involve rate limiting deaggregation of an LDA dimer.…”
mentioning
confidence: 92%
“…Knochel et al has exploited this effect by adding stoichiometric amounts of LiCl to conventional Grignard or Hauser reagents to induce an enhanced reactivity with respect to that of monometallic magnesium reagents. [2] Collum et al presented the surprising and profound role that LiCl plays in a series of deprotonation [3] and addition reactions, [4] establishing that LiCl catalysis is detectable with miniscule quantities of LiCl, and that "striking accelerations" (70 fold) are elicited by less than 1.0 mol % LiCl for 1,4-addition reactions of lithium diisopropylamide to unsaturated esters. [4] Despite this, firm structural evidence of the crucial halide-incorporated species that may be involved in these reactions is rare.…”
mentioning
confidence: 99%
“…[2] Collum et al presented the surprising and profound role that LiCl plays in a series of deprotonation [3] and addition reactions, [4] establishing that LiCl catalysis is detectable with miniscule quantities of LiCl, and that "striking accelerations" (70 fold) are elicited by less than 1.0 mol % LiCl for 1,4-addition reactions of lithium diisopropylamide to unsaturated esters. [4] Despite this, firm structural evidence of the crucial halide-incorporated species that may be involved in these reactions is rare. [1h, 5] In one example, we recently synthesized and characterized the magnesiate [(thf) 2 Li(m-Cl) 2 Mg(TMP)(thf)] and found that it functions identically to Knochels in situ Grignard system (TMP = 2,2,6,6-tetramethylpiperidide).…”
mentioning
confidence: 99%